CFD simulation of a packed bed industrial absorber with interbed liquid distributors. (April 2020) - Gbadago, Dela Quarme; Oh, Hyun-Taek; Oh, Dong-Hoon; Lee, Chang-Ha; Oh, Min
Highlights: CFD simulation for a pilot scale CO2 absorber with 5 packed beds was carried out using OpenFOAM. Using simplified absorber models cause deviations in simulation results from the actual operation data. Using multi-bed absorbers allow for thorough investigation and study of industrial absorbers. Liquid hold up of each bed is a key determiner of CO2 removal efficiency and absorber performance. Interbed liquid distributors act as internal baffles to enhance radial gas distribution. Abstract: CO2 absorption processes at industrial scale are usually carried-out in multi-bed columns. However, the design, modelling and simulation of CO2 absorbers are usually executed with simplified single bed columns that do not represent the full design realities of industrial-scale absorbers; limiting the applicability of such results to industrial processes. In this study, a CFD simulation of an MEA absorption process for the removal of CO2 gas on an AMT-SP 350Y structured packing was executed for an industrial-scale pilot plant. The CFD simulation was carried out for three different absorber configurations (Type A, Type B, and Type C). The liquid hydrodynamics, pressure drop, and CO2 removal efficiencies were studied and compared among the three types. Results from the Type A (single bed) and Type B (double bed) absorbers were found to have deviated from the actual plant data while the Type C, with 5-beds and four, interbed liquid distributors was observed to give the best performance as a true representation of the industrial absorber. A two-parameter validation in terms of pressure drop and CO2 removal efficiency was carried out between the pilot plant and the CFD simulation with a maximum discrepancy of 5.2% between the results. On the parametric study of the impact of varying CO2 loadings on absorption efficiencies, it was found and subsequently recommended that keeping the CO2 loading up to 30 mol % will ensure an efficient carbon capture. Further parametric studies were also performed to ascertain the effect of varying gas flow rates on the absorption process.